Impact of Standing Speed on the Peripheral and Central Hemodynamic Response to Orthostasis: Evidence From the Irish Longitudinal Study on Ageing. Issue 2 (February 2020) - O'Connor, John D.; O'Connell, Matthew D. L.; Nolan, Hugh; Newman, Louise; Knight, Silvin P.; Kenny, Rose Anne
Abstract : Assessment of the cerebrovascular and cardiovascular response to standing has prognostic value for a range of outcomes in the older adult population. Studies generally attempt to control for standing speed differences by asking participants to stand in a specified time but little is known about the range of transition times observed. This study aimed to characterize how standing speed associates with cardiovascular and cerebrovascular measures following transition from supine to standing. Continuous cerebral oxygenation, heart rate, systolic and diastolic blood pressure were monitored for 3 minutes after transitioning from supine to standing. An algorithm was used to calculate the time taken to transition from existing Finometer data (from the height correction unit). Linear mixed-effects models were used to assess the influence of transition time on each of the signals while adjusting for covariates. Transition time ranged from 2 to 27 s with 17% of participants taking >10 s to stand. Faster transition was associated with a more extreme decrease 10 s after standing but improved recovery at 20 s for cerebral oxygenation and blood pressure. Standing faster was associated with an elevated heart rate on initiation of stand and a quicker recovery 10 to 20 s after standing. The speed of transitioning from supine to standing position is associated with cardiovascular and cerebrovascular response in the early period after standing (<40 s). Care should be taken in the interpretation of findings which may be confounded by standing speed and statistical adjustment for standing time should be applied where appropriate. Abstract : Supplemental Digital Content is available in the text.